Value of Bone marrow Examination in Pyrexia of unknown origin - Jha, A; Sarda, R (Journal of Pathology of Nepal, 2013)
Background: Pyrexia of unknown origin is a common diagnostic dilemma. Series of diagnostic modalities are required to arrive at diagnosis. Bone marrow examination is one of the common tests implicated in the diagnosis in combination with other diagnostic modalities. Present study has attempted to explore the causes of pyrexia of unknown origin based on bone marrow morphological study. Materials and Methods: In a one year prospective study conducted at Manipal Teaching Hospital, Pokhara, Nepal; bone marrow aspiration and biopsy was performed and evaluated morphologically, in 57 patients fulfilling the criteria of classic pyrexia of unknown origin. Results: In 42% cases; specific diagnosis could be made and hematological neoplasm was the most common finding followed by megaloblastic anemia, hypoplastic anemia and one case each of hemophagocytosis, malaria and tuberculosis. Acute leukemia was the most frequently encountered hematological malignancy followed by multiple myeloma, chronic myeloid leukemia, essential thrombocythemia and myelodysplastic syndrome. Conclusion: Morphological examination of bone marrow has important role in diagnosis of pyrexia of unknown origin. However, yield of diagnosis can be increased if it is combined with other diagnostic modalities including radiological, microbiological and serological tests. DOI: http://dx.doi.org/10.3126/jpn.v3i6.8991 Journal of Pathology of Nepal (2013) Vol. 3, 447-451